High-flux composite nanofiltration membrane as well as preparation method and application thereof
Through the non-traditional forward interface polymerization method, the "tradition-of-weight" effect and structural inhomogeneity of traditional nanofiltration membranes are solved, and a high-throughput, highly hydrophilic composite nanofiltration membrane is prepared, which is suitable for a variety of water treatment applications.
Patent Information
- Application Number
- CN202510118380.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-11
AI Technical Summary
Existing polyamide nanofiltration membranes have a "trade-off" effect between permeability and selectivity, and traditional interface polymerization technology is sensitive to condition changes, affects controllability, and may lead to uneven membrane structure and hollow defects.
Using non-traditional forward interface polymerization method, the nanofiber membrane is fixed on the isolation support, and the excess aqueous phase is first immersed in the aqueous phase solution, and then inverted into the organic phase system to react to form a dense polyamide separation layer to avoid hollow defects.
The prepared composite nanofiltration membrane has a thinner surface, higher water flux and retention rate, stronger hydrophilicity, and has a complete and defect-free structure. It is suitable for seawater desalination, drinking water purification and industrial wastewater treatment.
Smart Images

Figure BDA0005258355970000081 
Figure BDA0005258355970000101 
Figure BDA0005258355970000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite nanofiltration membranes, and in particular to a high-flux composite nanofiltration membrane and a preparation method and application thereof. Background Art
[0002] In recent years, the global water shortage problem has become increasingly severe, and water environment issues have received increasing attention. Membrane separation technology is known for its high efficiency, energy saving, no phase change, and easy integration with other technologies. It has been widely used in fields such as seawater desalination and high-salinity wastewater recovery. Among these technologies, nanofiltration (NF) represents a new type of membrane separation technology that builds a bridge between reverse osmosis (RO) and ultrafiltration (UF). The permeability of nanofiltration membranes is significantly higher than that of reverse osmosis membranes, while operating at lower pressures. Through mechanisms such as size retention, Donnan effect, and charge interaction, they can also effectively intercept high-value organic compounds in water. In addition, nanofiltration membranes can selectively separate organic compounds based on molecular weight and charge, so they are promising in freshwater treatment.
[0003] The interfacial polymerization (IP) method is widely used to manufacture commercial polyamide nanofiltration membranes. The basic principle is that a condensation reaction occurs at the immiscible water-oil interface, and an aqueous solution of amine monomers (such as piperazine (PIP) or metaphenylenediamine (MPD)) reacts with an organic solution containing an acyl chloride monomer (such as trimesoyl chloride (TMC) or metaphenylenediamine chloride) to form a dense polyamide separation layer. During the IP process, the strong nucleophilicity and electrophilicity of the monomers lead to a violent irreversible reaction, forming a relatively rough structure with uneven polymer density and charge distribution in the polyamide layer. This leads to an obvious "trade-off" effect between the permeability and selectivity of polyamide nanofiltration membranes. In addition, the traditional polyamide nanofiltration membrane layer is usually several hundred nanometers thick, resulting in a large filtration resistance, a rapid decrease in permeate flux during extended desalination, and multiple potential scaling points, which further reduces the membrane separation efficiency. Therefore, the development of ultra-thin, smooth, and high filtration resistance membranes has become a recent research hotspot.
[0004] However, due to the sensitivity of interfacial polymerization reactions to changes in conditions such as temperature, pH, monomer concentration, and polymerization time, some adjustment strategies (introducing additives or constructing intermediate layers) may impair the controllability of the polymerization process and affect the progress of the interfacial polymerization (IP) reaction. In addition, the toxicity of certain additives also raises concerns about potential environmental risks. Recently, researchers have explored optimizing interfacial polymerization conditions, such as ice-enclosed interfacial polymerization (IC-IP) strategy and optimizing polymerization pH, to form a unique polyamide (PA) layer structure and improve membrane performance. These studies have shown that adjusting IP process conditions can significantly affect the overall performance of the membrane, thereby developing a simpler method for manufacturing high-performance polyamide nanofiltration membranes.
[0005] Currently, the development of high-performance composite nanofiltration membranes mainly relies on the optimization of traditional interfacial polymerization technology (IP-F). Traditional forward interfacial polymerization technology is to immerse the porous support layer in an aqueous solution, and then introduce an oil phase reaction solution, with the oil phase floating on the water phase. Professor Hsiao's research group first used reverse interfacial polymerization (IP-R) to advance this method, that is, changing the position of the two immiscible phases. In their method, the nanofiber membrane is first soaked in an oil phase solution, and after removing the excess oil phase solution, a large amount of water phase solution is poured, and the water phase is placed on the oil phase. Studies have shown that during the IP-R process, the water phase reaction monomers cross the interface between the two phases and react on the oil phase side. At the same time, the organic phase solvent with a lower density rises to the interface. Under the same conditions, this reverse movement of the two-phase reaction monomers accelerates the interfacial reaction rate, making it more feasible to produce a thinner epidermal layer. This method also enhances the direct adhesion between the surface functional layer and the porous base membrane. However, due to the volatility of the organic phase and the gravity effect of the aqueous phase, tiny void defects may appear in the polyamide functional layer, which will cause permeability problems and penetration problems with reduced salt rejection rate in the desalination process. Summary of the invention
[0006] In view of the above-mentioned shortcomings of the prior art, the present invention develops a new interfacial polymerization method, namely, non-traditional forward interfacial polymerization, to solve the problems in the prior art.
[0007] To achieve the above objectives and other related objectives, the present invention is achieved through the following technical solutions.
[0008] The first aspect of the present invention provides a method for preparing a composite nanofiltration membrane, comprising the following steps:
[0009] 1) fixing the nanofiber membrane on an isolation carrier, then immersing the nanofiber membrane in an aqueous solution, and then taking out and removing excess aqueous solution on the surface of the nanofiber membrane to obtain a treated membrane A;
[0010] 2) Inverting the treated membrane A and soaking it in an organic phase solution, and the aqueous phase solution soaked on the nanofiber membrane undergoes an interfacial polymerization reaction with the organic phase solution to obtain a treated membrane B;
[0011] 3) heat-treating the treated membrane B to obtain a composite nanofiltration membrane.
[0012] In the present invention, the nanofiber membrane fixed on the isolation carrier is first immersed in an aqueous solution, and after removing excess aqueous solution, the nanofiber membrane fixed on the carrier is inverted and immersed in an organic phase system for reaction. The inverted nanofiber membrane is located below the carrier. The composite nanomembrane prepared based on this method is complete and has no void defects.
[0013] In some embodiments, the nanofiber membrane is a nanofiber membrane obtained by electrospinning.
[0014] In certain embodiments, the nanofiber membrane is a hydrophilic nanofiber membrane.
[0015] In certain embodiments, the nanofiber membrane is at least one of a polyacrylonitrile (PAN) nanofiber membrane, a polysulfone nanofiber membrane, and a polyethersulfone nanofiber membrane.
[0016] In some embodiments, the molecular weight of the polymer material in the nanofiber membrane is 90,000 g / mol to 200,000 g / mol; it can also be 1290,000 g / mol to 180,000 g / mol.
[0017] In certain preferred embodiments, the nanofiber membrane is a polyacrylonitrile nanofiber membrane.
[0018] In certain embodiments, the nanofiber membrane is prepared by preparing a PAN electrospinning solution with a mass fraction of 10 to 20 wt%, and performing electrospinning to obtain the nanofiber membrane.
[0019] In certain embodiments, the electrospinning process parameters are: voltage 20-24 kV, propulsion rate 15-20 μL / min, spinning solution volume 4-8 ml and / or receiving drum speed 60-100 r / min.
[0020] In certain embodiments, the aqueous solution includes an amine compound and an acid absorbent.
[0021] In certain embodiments, the amine compound is at least one of piperazine (PIP), meta-phenylenediamine, polyethyleneimine (PEI), ethylenediamine, and phenylenediamine; preferably piperazine.
[0022] In some embodiments, the acid absorbent is at least one of tripropylamine, triethylamine, N,N-diisopropylethylamine, calcium bicarbonate, and sodium hydroxide, preferably triethylamine. The present invention introduces the above acid absorbent to neutralize HCl generated in the polymerization reaction of generating the active separation layer, thereby promoting the polymerization reaction to proceed smoothly.
[0023] In certain embodiments, the concentration of the amine compound in the aqueous phase solution is 0.2-2wt%; it can also be 0.2-1wt%; it can also be 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.5wt%, 2wt%; if the concentration is too high, the formed membrane will be very thick and the water flux will be greatly reduced; if the concentration is too low, the formed membrane will not be dense enough and cannot retain salt.
[0024] In certain embodiments, the concentration of the acid absorbent in the aqueous solution is 0.5-1.5wt%; it can also be 0.5-1wt%, it can also be 1-1.5wt%, it can also be 0.8-1.2wt%, it can also be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%.
[0025] In certain embodiments, the mass ratio of the amine compound to the acid absorbent is 0.2-2:1; it can also be 0.2-1:1; it can also be 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.5:1, 2:1.
[0026] In certain embodiments, the aqueous solution further comprises an inorganic salt.
[0027] In certain embodiments, the inorganic salt comprises a calcium salt; preferably calcium chloride. 2 Complexation reaction between + ions and carbonyl groups in TMC monomers and the selective separation layer.
[0028] In certain embodiments, the concentration of calcium chloride in the aqueous solution is 5-20wt%; it can also be 5-15wt%; it can also be 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%.
[0029] In certain embodiments, the organic solution includes an acyl chloride compound; wherein the acyl chloride compound and the amine compound undergo a polymerization reaction to form a dense polyamide separation layer.
[0030] In certain embodiments, the acyl chloride compound is at least one of trimesoyl chloride (TMC), adipoyl chloride, and isophthaloyl chloride; preferably trimesoyl chloride.
[0031] In certain embodiments, the solvent of the organic solution is an organic solvent; preferably at least one of n-hexane, cyclohexane, n-heptane, petroleum ether, and dichloromethane.
[0032] In certain embodiments, based on the total mass of the organic solution, the concentration of the acyl chloride compound in the organic solution is 0.1-0.5wt%, or 0.1-0.3wt%, or 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, or 0.5wt%.
[0033] In certain embodiments, the infiltration time in step 1) is 40 to 80 s; it may also be 50 to 70 s, or it may be 40 s, 45 s, 50 s, 55 s, 60 s, 65 s, 70 s, 75 s, or 80 s.
[0034] In certain embodiments, the infiltration time in step 2) is 20 to 40 s; it can also be 25 to 35 s, or it can be 20 s, 25 s, 30 s, 35 s, or 40 s; wherein the infiltration time is the reaction time of interfacial polymerization. Too long a time will result in a thicker film, while too short a time will result in uneven film formation.
[0035] In some embodiments, the heat treatment temperature is 50-70°C; it can also be 55-65°C, or 50°C, 55°C, 60°C, 65°C, or 70°C. The heat treatment is a post-treatment process of interfacial polymerization. High heat treatment temperature and long time will make the membrane thicker and denser, the water flux will decrease, and the salt rejection rate will increase. Short time and low temperature will reduce the cross-linking density, increase the membrane water flux and reduce the salt rejection rate.
[0036] In certain embodiments, the heat treatment time is 10 to 20 min; it can also be 13 to 18 min, or it can be 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min, or 20 min.
[0037] In certain embodiments, the isolation carrier is made of a material that is impermeable to water and organic phase, and may be a glass plate or a polytetrafluoroethylene plate.
[0038] The second aspect of the present invention provides a composite nanofiltration membrane obtained by the above-mentioned preparation method.
[0039] The third aspect of the present invention provides the application of the composite nanofiltration membrane obtained by the above-mentioned preparation method in the field of water treatment; specifically, it is used in seawater desalination pretreatment, drinking water purification, industrial and / or domestic wastewater treatment, food industry and / or medicine.
[0040] Beneficial effects:
[0041] The present invention provides a method for preparing a high-flux negatively charged nanofiltration membrane by non-traditional forward interfacial polymerization; this method mainly involves inverting a nanofiber membrane coated with an aqueous solution and fixed on an isolation carrier so as to completely contact the surface of an organic phase solution to prepare a high-flux negatively charged nanofiltration membrane; and the present invention further adds an inorganic salt CaCl2 to the aqueous solution to successfully prepare a composite nanofiltration membrane with higher permeability. Experimental results show that compared with traditional methods, the composite nanofiltration membrane produced by this non-traditional forward interfacial polymerization method has a thinner surface, higher water flux and interception rate, and stronger hydrophilicity; it can be widely used in industrial and domestic wastewater treatment; it can also be used in drinking water purification, seawater desalination, food industry, medicine and other fields, and has broad prospects for industrial application. By optimizing the interfacial polymerization process, the present invention provides a new direction and technical support for the future development of high-performance nanofiltration membranes. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 Shown is a schematic diagram of the preparation process of traditional forward interfacial polymerization (IP) and non-traditional forward interfacial polymerization (NIP) nanofiltration membranes. Figure 1 a: Reaction between piperazine (PIP) and trimesoyl chloride (TMC); Figure 1 b: Schematic diagram of preparing composite nanofiltration membrane by IP method and NIP method.
[0043] Figure 2 Shown are the surface morphology and cross-sectional images of traditional forward interfacial polymerization and non-traditional forward interfacial polymerization nanofiltration membranes. Figure 2 a: Surface scanning electron microscopy image of traditional forward interfacial polymerization nanofiltration membrane; Figure 2 b: Surface scanning electron microscopy image of non-traditional forward interfacial polymerization nanofiltration membrane (the nanocavity is inside the dotted line); Figure 2 c: Cross-sectional SEM image of conventional forward interfacial polymerization nanofiltration membrane; Figure 2 d: Cross-sectional SEM image of the non-traditional forward interfacial polymerization nanofiltration membrane; Figure 2 e is an atomic force microscope image of a conventional forward interfacial polymerization nanofiltration membrane (with a three-dimensional atomic force microscope image inserted); Figure 2 f is an atomic force microscopy image of a non-conventional forward interfacial polymerization nanofiltration membrane (with a three-dimensional atomic force microscopy image inserted).
[0044] Figure 3 The surface morphology and cross-sectional view of the non-traditional forward interfacial polymerization separation composite nanofiltration membrane are shown at different monomer addition amounts. Figure 3 a1: Surface SEM image of composite nanofiltration membrane NIP-0.2; Figure 3 b1: SEM image of the cross section of the composite nanofiltration membrane NIP-0.2; Figure 3 a2: Surface scanning electron microscope image of composite nanofiltration membrane NIP-1; Figure 3b2: SEM image of the cross section of the composite nanofiltration membrane NIP-1; Figure 3 a3: Surface scanning electron microscope image of composite nanofiltration membrane NIP-2; Figure 3 b3: Scanning electron microscopy image of the cross section of the composite nanofiltration membrane NIP-2.
[0045] Figure 4 Shown are the (a) pore size distribution diagram, (b) surface Zeta point, (c) contact angle and (d) pure water flux test data diagram of the non-traditional positive empty interface polymerization composite nanofiltration membrane; Figure 4 a: Evaluation of the MOWCO curves of IP-1 and NIP-0.5 membranes using PEG molecules of different molecular weights (1000 ppm, 0.5 MPa); Figure 4 b: Zeta potential of IP-1 and NIP-0.5 membranes at different pH values; Figure 4 c: Statistics of water contact angles of IP-1, NIP-0.2, NIP-0.5, NIP-1, and NIP-2 composite nanofiltration membranes; Figure 4 d: Pure water permeability statistics of IP-1, NIP-0.2, NIP-0.5, NIP-1, and NIP-2 composite nanofiltration membranes.
[0046] Figure 5 The figure shows the cross-flow test data of the non-traditional forward empty interface polymerization composite nanofiltration membrane using a cross-flow device at different monomer addition amounts, which illustrates the effect of different ratios on the separation performance of Na2SO4 and NaCl; Figure 5 a: penetration statistics, Figure 5 b: interception rate statistics; Figure 5 c: Separation performance statistics of different salts of IP-1 composite nanofiltration membrane; Figure 5 d: Separation performance of NIP-0.5 composite nanofiltration membrane for different salts.
[0047] Figure 6 Shown is the performance test of NIP-0.5 membrane; Figure 6 a: Long-term stability performance test conducted with 2000ppm Na2SO4 solution at 0.5MPa working pressure; Figure 6 b: Pressure test of different working pressures of 2000ppm Na2SO4; Figure 6 c: Retention rate test of Na2SO4 solution with different concentrations; Figure 6 d: Antifouling performance test using 1000 ppm BSA solution.
[0048] Figure 7 The surface morphology and cross-section of the composite nanofiltration membrane after the addition of CaCl2 to the non-traditional forward empty interface polymerization composite nanofiltration membrane are shown; Figure 7a: Surface scanning electron microscope image of Ca-NIP-0.5 composite nanofiltration membrane, Figure 7 b: Surface scanning electron microscope image of NIP-0.5 nanofiltration membrane; Figure 7 c: Scanning electron microscopy image of the cross section of Ca-NIP-0.5 composite nanofiltration membrane.
[0049] Figure 8 Shows the effect of different CaCl2 addition amounts on the separation performance of Na2SO4 and NaCl (2000ppm, 0.5MPa) of non-traditional forward interfacial polymerization composite nanofiltration membrane: Figure 8 a: penetration statistics, Figure 8 b: interception rate statistics; Figure 8 c: Long-term nanofiltration test of Na2SO4 solution (2000 ppm, 0.5 MPa); Figure 8 d: Pressure resistance test at different operating pressures of Na2SO4 solution (2000ppm).
[0050] Fig. 9 Schematic diagram of bubble generation on the surface of NIP membrane. DETAILED DESCRIPTION
[0051] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.
[0052] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods in the following examples without specifying specific conditions are generally carried out under conventional conditions or under conditions recommended by the manufacturers.
[0053] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.
[0054] Reverse interfacial polymerization (IP-R) means that the nanofiber membrane is first soaked in an oil phase solution, and then a large amount of water phase solution is poured after removing the excess oil phase solution. Since the organic phase is added first, the organic phase will evaporate and be lost in this process. The volatility of the organic phase and the gravity effect of a large amount of water phase may cause tiny void defects in the polyamide functional layer, resulting in a significant decrease in the salt interception rate.
[0055] In view of the above problems, the present invention provides a high-flux nanofiltration membrane prepared by a non-traditional forward interfacial polymerization method, and a preparation method and application thereof. The method is to first add an aqueous phase to the nanofiber membrane, remove excess aqueous phase solution, place the treated membrane A above the organic phase monomer solution, and then enter the organic phase system to react so that the organic phase is below the aqueous phase. At this time, the organic phase is excessive and the aqueous phase is appropriate, that is, the amount of aqueous phase and oil phase used is different from that of reverse interfacial polymerization. The nanofiltration membrane prepared by the non-traditional forward interfacial polymerization method of the present invention is complete and has a high salt rejection rate.
[0056] Exemplarily; the present invention fixes a nanofiber membrane coated with an aqueous solution on a glass plate (which can be replaced by other impermeable carriers) so that the nanofiber membrane containing the aqueous solution is above the glass plate, inverts (or flips upside down), places the nanofiber membrane below the glass plate, and then immerses it in an organic phase system for reaction; at this time, the glass plate support layer is above the nanofiber membrane, and when the nanofiber membrane below the glass plate contacts the organic phase, the organic phase is below the aqueous phase; if the glass plate is not flipped, the nanofiber membrane coated with an aqueous solution fixed on the glass plate is directly introduced into the organic phase system for reaction, and at this time, the glass plate support layer is below the nanofiber membrane, and when the nanofiber membrane below the glass plate contacts the organic phase, the organic phase is above the nanofiber membrane, and at this time, the organic phase is above the aqueous phase, which will result in a density difference without gravity, a slow diffusion rate, and tiny defects and penetration problems in the polyamide functional layer.
[0057] Experimental tests show that the high-flux nanofiltration membrane provided by the present invention has a thinner surface, higher water flux and interception rate, and stronger hydrophilicity; this improvement is attributed to the enhanced ability of the amine monomer to diffuse from the water phase to the organic phase under the action of gravity, thereby accelerating the interfacial polymerization reaction between the amine compound and the acyl chloride compound, effectively blocking the heat dissipation, and making the polyamide (PA) selective separation layer thinner. At the same time, the movement of the water-oil interface position, coupled with the low density and high volatility of the organic phase, causes interface deformation when the water phase infiltrates under the action of gravity.
[0058] In addition, due to the regulatory effect of inorganic salt particles on the interfacial polymerization process, the same method was used to add inorganic salt CaCl2 to the aqueous solution to successfully prepare a composite nanofiltration membrane with higher permeability.
[0059] Material:
[0060] Polyacrylonitrile (PAN, Mw = 150,000 g / mol) was obtained from BASF SE. N,N-dimethylformamide (DMF, AR), triethylamine (TEA, AR), magnesium chloride (MgCl2, AR), calcium chloride (CaCl2, AR) and polyethylene glycol (PEG, CP) were obtained from China National Pharmaceutical Group Chemical Reagent Co., Ltd. Piperazine (PIP, 99%), 1,3,5-benzyltrimethyl chloride (TMC, 98%), n-hexane (≥97%), sodium sulfate (Na2SO4, 99%), magnesium sulfate (MgSO4, ≥99.5%) and sodium chloride (NaCl, ≥99.5%) were purchased from Shanghai Titan Technology Co., Ltd. Bovine serum albumin (BSA, 98%) was purchased from J&K Ultrafine Materials Co., Ltd.
[0061] Characterization method: The surface and cross-sectional morphology of the composite membranes were characterized using a field emission scanning electron microscope (FE-SEM, HITACHI, Japan). The surface hydrophilicity of the PAN nanofiber-based membrane and the composite membrane was evaluated by a dynamic contact angle tester (OCA40, Germany), and the average value was taken after testing at three random positions. The surface potential of each composite membrane was characterized by a solid surface streaming potential test system (SurPASS 3, Austria), and each membrane was tested three times and the average value was taken.
[0062] The nanofiber membrane used in this embodiment is prepared by an electrospinning method, and the specific steps are as follows:
[0063] PAN powder with a molecular weight of 150,000 was placed in a vacuum oven and dried at 60°C for 12 hours to remove excess moisture. 12 g of the dried PAN powder was added as a solute into 88 g of DMF and magnetically stirred at 60°C for 12 hours to obtain a uniform 12 wt% PAN electrospinning solution.
[0064] Then, 5 mL of the solution was taken with a sterile syringe for electrospinning. The needle size was 0.7×32 mm. The syringe push speed was set to 16 μL / min, the electrospinning voltage was 22-24 kV, the spinning collection drum speed was 80-120 r / min, and the humidity and temperature were maintained at 45-50% and 25-30 ° C, respectively. After spinning, the PAN membrane was placed in an oven for 12 hours to remove residual DMF. In order to improve the mechanical strength and provide a smooth surface for the preparation of the top separation layer, the PAN nanofiber scaffold as the support layer was cold pressed at 5 MPa for 60 seconds at room temperature; the nanofiber membrane was prepared.
[0065] Figure 1 The figure shows the schematic diagram of the preparation process of the traditional forward interfacial polymerization (IP) and non-traditional forward interfacial polymerization (NIP) nanofiltration membrane. Figure 1a is the reaction between piperazine (PIP) and trimesoyl chloride (TMC); Figure 1 b is a schematic diagram of preparing a composite nanofiltration membrane by IP method and NIP method. The present invention prepares a non-traditional forward interfacial polymerization nanofiltration membrane and a composite nanofiltration prepared by traditional forward interfacial polymerization through Example 1 and Comparative Example 1, respectively.
[0066] Example 1
[0067] This example uses a non-traditional forward interfacial polymerization method to prepare a composite nanofiltration membrane. The specific method is as follows:
[0068] First, place the nanofiber membrane on the glass plate and clamp it with a clamp, then soak the nanofiber membrane in water for 1 minute. After removing the excess water, soak the surface of the nanofiber membrane with a layer of water solution of different proportions (PIP: 0.2wt%, 0.5wt%, 1wt%, 2wt%, TEA: 1wt%, solvent is water). Turn the glass plate upside down, at this time the nanofiber membrane is located below the glass plate, and then immerse the nanofiber membrane in an organic phase solution (TMC: 0.2wt%, solvent is n-hexane) for 30 seconds to complete the interfacial polymerization reaction and form a dense and uniform polyamide (PA) separation layer. The polymerized composite membrane is placed in a 60°C forced air drying oven for 15 minutes of thermal crosslinking; the names of the composite nanofiltration membranes with different proportions are shown in Table 1.
[0069] Table 1
[0070]
[0071] Comparative Example 1
[0072] The composite nanofiltration membrane is prepared by conventional forward interfacial polymerization method, which includes the following steps:
[0073] First, place the nanofiber membrane on a glass plate and clamp it with a clamp. Then soak the nanofiber membrane in water for 1 minute. After removing the excess water, apply a 1wt% PIP aqueous solution (PIP: 1wt%, TEA: 1wt%, solvent is water) on the surface of the nanofiber membrane. Then, pour an organic phase solution with a concentration of 0.2wt% TMC on the membrane surface. After 1 minute of interfacial polymerization reaction, a dense PA separation layer is formed. Finally, the polymerized composite membrane is placed in a 60°C forced air drying oven for 15 minutes of thermal crosslinking. The name of the composite nanofiltration membrane formed is shown in Table 1.
[0074] Effect Example 1
[0075] The surface and cross-sectional morphology of the composite membranes were characterized using field emission scanning electron microscopy (FE-SEM, HITACHI, Japan). When the IP-1 composite nanofiltration membrane was prepared by the conventional forward interfacial polymerization (IP) method, many interlaced worm-like structures were clearly visible on the membrane surface ( Figure 2 a). This morphology is caused by the uniform distribution of a large number of PIP monomers during the interfacial polymerization process. After characterizing the cross-sectional morphology of the composite nanofiltration membrane, it was found that the separation layer height of the IP-1 composite membrane prepared by the conventional forward interfacial polymerization method was about 117nm ( Figure 2 c). In contrast, the membrane (NIP-0.5) prepared by the non-conventional forward interfacial polymerization (NIP) method has relatively few surface wrinkles ( Figure 2 b), the film thickness is reduced to 72nm ( Figure 2 d), the nanofiber structure under the PA separation layer can be clearly observed. The reason for this phenomenon is that during the interfacial polymerization, the solubility of PIP monomer in n-hexane is greater than that of TMC monomer in water, and PIP monomer diffuses into the organic phase, and gravity further accelerates this process. At the same time, the TMC monomer in the organic phase rises due to its lower density, which strengthens the monomer diffusion and accelerates the interfacial polymerization, thus forming a thin selective separation layer.
[0076] When the aqueous monomer comes into contact with a large amount of organic phase solution, the aqueous monomer diffuses rapidly into the organic phase under the action of gravity. This rapid diffusion causes PIP and TMC to react rapidly, forming a dense PA layer that effectively blocks the dissipation of heat. The accumulated heat at the interface generates bubbles, which are eventually wrapped by the dense PA layer to form a crater-like structure ( Fig. 9 ).
[0077] In addition, many crater-like structures with a size of about 2 μm were observed on the surface of the NIP-0.5 composite membrane. This is because the interfacial polymerization reaction has an exothermic nature; when the membrane encounters a large amount of organic phase solution, the aqueous monomer is accelerated and diffuses into the membrane under the action of gravity. In addition, even if the concentration of the PIP monomer is adjusted, many pit-like structures can still be seen on the surface of the composite nanofiltration membrane ( Figure 3 a1-a3). As the PIP concentration increases, the thickness of the PA separation layer gradually increases ( Figure 3 b1-b3). The measured PA layer thicknesses are: NIP-0.2: 65nm, NIP-1: 79nm and NIP-2: 113nm.
[0078] In order to further study the microscopic surface morphology of the PA separation layer prepared by the forward and non-conventional interfacial polymerization methods, the surfaces of IP-1 and NIP-0.5 composite nanofiltration membranes were characterized using atomic force microscopy. According to previous studies, PA layers with pit-like structures usually exhibit higher surface roughness due to the large contact area generated by the annular pit structure. However, the crater-like structure formed during the NIP process is not concentrated on the membrane surface, which is due to the rapid volatilization of the organic phase that wraps the bubble cavities generated on the interface of the PA layer. Figure 2 As shown in Figures 2e and 2f, the surface of the NIP composite nanofiltration membrane is smoother. The average surface roughness (Ra) values of the IP-1 and NIP-0.5 composite membranes are 102±7nm and 68±10nm, respectively. Generally speaking, the lower the Ra value, the stronger the antifouling performance. The smoother membrane surface can not only reduce the occurrence of concentration polarization, but also minimize the accumulation of pollutants and the irreversible fouling caused by the pollutants being retained in the uneven structure of the membrane.
[0079] Effect Example 2
[0080] 1. The molecular weight cutoff (MWCO) and pore size distribution of IP-1 and NIP-0.5 composite nanofiltration membranes were evaluated by testing the retention rate of 1000 ppm polyethylene glycol (PEG) solutions with different molecular weights (200, 300, 600, and 1000 Da).
[0081] The molecular weight cutoff (MWCO) of the composite membrane was evaluated by calculating the rejection rate of the composite membrane for PEG of different molecular weights (200-1000 Da). According to the definition, when the rejection rate reaches 90%, the corresponding PEG molecular weight is regarded as the molecular weight cutoff of the composite membrane.
[0082] The results are as follows Figure 4 When the retention rate reaches 90%, the corresponding PEG molecular weight is considered to be the molecular weight cutoff of the composite nanofiltration membrane. The results show that the molecular weight cutoff of IP-1 membrane is slightly lower than that of NIP-0.5, which are 257Da and 281Da respectively.
[0083] The cut-off molecular weight of the test membrane reflects the effective pore size of the membrane. The calculation method is as follows. When the retention rate is 90%, it is achieved by a solution containing 1g / L of PEG with different molecular weights. The PEG concentration in the feed liquid and the filtrate is measured by a TOC analyzer, and the pore size distribution (d p ), the calculation formula is as follows:
[0084]
[0085] Wherein, dp is the average effective pore size of the composite nanofiltration membrane, μp is the average effective pore radius of PEG when the retention rate R is 50%, and the geometric standard deviation σp of the membrane is the ratio of the Stoke's diameter when the PEG retention rate is 84.13% and 50%.
[0086] The Stoke's radius of PEG is calculated by formula (2).
[0087] r=16.73×M 0.557 ×10 -12 (2);
[0088] Wherein, r is the Stokes radius of the composite nanofiltration membrane (m), and M is the molecular weight cutoff value of PEG (Da).
[0089] The average effective pore sizes of the two composite nanofiltration membranes were calculated to be 0.5388 nm and 0.5719 nm, respectively, which indicates that the two preparation methods have little effect on the pore size of the composite nanofiltration membranes.
[0090] The calculated geometric standard deviation values (σp) are all less than 1.3, indicating that the pore size distributions of the two composite nanofiltration membranes are narrower and more uniform, thus making the composite nanofiltration membranes have more stable filtration performance.
[0091] 2. The surface potential of the composite membrane was characterized by a solid surface streaming potential test system (SurPASS 3, Austria). Each membrane was tested three times and the average value was taken. The surface charge characteristics of the composite nanofiltration membrane were analyzed by measuring the Zeta potential at different pH values.
[0092] The results are as follows Figure 4 As shown in Figure b, the surface charges of both membranes are negative, and the negative value decreases with increasing pH. It is worth noting that the composite nanofiltration membrane prepared using the NIP method has a more obvious negative charge. This negative charge is attributed to the hydrolysis of the acyl chloride groups present in the unreacted TMC monomers. In addition, during the preparation of the NIP-0.5 composite nanofiltration membrane, the immersion of a large amount of organic phase solution and the reduction of the PIP monomer concentration in the aqueous phase led to an increase in the number of unreacted TMC monomers on the membrane surface. Therefore, more acyl chloride groups were hydrolyzed to carboxyl groups.
[0093] 3. The surface hydrophilicity of the composite membrane was evaluated by a dynamic contact angle tester (OCA40, Germany), and the average value was taken after testing at four random positions. The contact angles of composite nanofiltration membranes with different ratios were also measured.
[0094] The results are as follows Figure 4c; The results show that at the same ratio, the contact angle of the composite nanofiltration membrane prepared by the NIP method is lower than that of the IP method, decreasing from 50.1° to 41.4°. Adjusting the concentration of PIP monomer in the aqueous solution will further affect the contact angle of the NIP composite nanofiltration membrane. When the PIP:TMC ratio in the composite membrane is 0.5:0.2 (NIP-0.5), the contact angle of the composite nanofiltration membrane reaches the lowest value of 35.6°. As the concentration of PIP monomer increases, the contact angle continues to decrease.
[0095] 4. The hydrophilicity of the composite nanofiltration membrane was further evaluated using a cross-flow device. The membrane was cut into appropriate sizes and installed on a cross-flow device, and pre-pressed for a period of time at a pressure of 6 bar to stabilize the permeability of the membrane. The pressure was then adjusted to 5 bar, and the pure water flux and permeability of the composite nanofiltration membrane were tested at this pressure. The calculation results are as follows:
[0096]
[0097] Where P represents the pure water flux or permeability of the composite nanofiltration membrane (L m -2 -h -1 bar -1 ), V(L) is the volume of solution passing through the effective area of the composite nanofiltration membrane within a certain period of time (L), Δt(h) is the running time, and A is the effective filtration area of the composite nanofiltration membrane (the effective filtration area in this experiment is 3.4×10 -4 m 2 )Δp(bar) is the operating pressure.
[0098] The retention of different salts was also tested by a cross-flow device, where the concentration of Na2SO4, MgSO4, MgCl2 and NaCl solutions was 2000 ppm.
[0099] The retention rate of the composite nanofiltration membrane is given by the following formula:
[0100]
[0101] Among them, R is the rejection rate of composite nanofiltration membrane for different salts, C p and C f Represents the concentration (ppm or mg / L) or conductivity (μs / cm) of the feed solution and permeate solution, respectively.
[0102] The results are as follows Figure 4 d; The results show that compared with the IP-1 composite nanofiltration membrane, at the same ratio, the pure water flux of the NIP-1 composite nanofiltration membrane increased from 12.7 L m -2 -h -1 bar -1(LMHB) increased to 22.2LMHB. In the NIP method, the pure water flux is also affected by the PIP monomer concentration. The pure water flux of NIP-0.5 composite nanofiltration membrane is the highest at 24.5LMHB. The enhancement of the permeability of NIP composite nanofiltration membrane can be attributed to two factors. First, the increase in hydrolyzed carboxyl groups on the membrane surface causes the hydroxyl (-OH) and carbonyl (C=O) groups in these carboxyl groups to form hydrogen bonds with water molecules, thereby increasing the hydrophilicity of the membrane. Second, during the non-traditional interfacial polymerization process, the crater-like structure formed in the polyamide layer provides an additional channel for the transmission of water molecules, reduces resistance, and facilitates the rapid passage of water through the polyamide layer. The pure water fluxes of NIP-0.2 and NIP-2 are 23.7 and 19.9LMHB, respectively, which are consistent with the above contact angle test results. When the PIP monomer concentration exceeds 0.5wt%, the flux of the composite nanofiltration membrane gradually decreases, but it is still higher than that of the membrane prepared by the traditional interfacial polymerization method.
[0103] Effect Example 3
[0104] In order to evaluate the separation performance of the composite nanofiltration membrane, the permeability and rejection of several typical inorganic salts were tested using a cross-flow device.
[0105] Figure 5 Figures 5a and 5b show the permeability and separation performance of different composite nanofiltration membranes for 2000ppm Na2SO4 and NaCl solutions at 0.5 MPa, respectively. The permeation flux measurements of different membranes for Na2SO4 are as follows: 11.0 (IP-1), 19.6 (NIP-0.2), 20.3 (NIP-0.5), 16.7 (NIP-1) and 15.7LMHB (NIP-2). The results show that at the same permeability ratio, the permeability flux of the NIP-1 composite nanofiltration membrane is significantly higher than that of the IP-1 membrane, while the permeability ratio of the NIP-0.5 membrane is the best. The increase in the permeability of the composite nanofiltration membrane can be attributed to the reduction in the thickness of the polyamide layer and the enhancement of hydrophilicity. However, as the thickness of the polyamide layer increases, the permeability of the composite nanofiltration membrane also decreases.
[0106] Compared with the traditional forward interfacial polymerization method, the nanofiltration membrane flux prepared using the NIP method is significantly improved and maintains a high rejection rate. The rejection rate of all membranes for Na2SO4 remains at around 98%, among which the rejection rate of the NIP-0.5 membrane is as high as 99.1%. This is because the NIP method produces more negatively charged membrane surfaces, which enhances the suppression of high-valent anions and minimizes the impact of the trade-off effects usually associated with increasing permeate flux.
[0107] The nanofiltration performance of the composite nanofiltration membranes (IP-1 and NIP-0.5) prepared by the two methods was further tested using four typical salt solutions at 0.5 MPa. The results are as follows: Figure 5c and 5d, all composite nanofiltration membranes have higher rejection rates for Na2SO4 and MgSO4 than for MgCl2 and NaCl solutions. Specifically, the rejection rates of NIP-0.5 composite nanofiltration membrane for Na2SO4 and MgSO4 are 99.1% and 94.8%, respectively, while the rejection rates for MgCl2 and NaCl are 74.7% and 22.8%, respectively. Figure 5 d). These results are consistent with the characteristics of negatively charged separation membranes, that is, they strongly repel high-valent anions and attract high-valent cations, which corresponds to the Zeta potential test results of the composite nanofiltration membrane. In addition, in addition to the stronger electronegativity of divalent ions and the stronger electrostatic repulsion, the retention of salt solutions is also affected by the pore size screening effect. Among the four typical salt solutions, NaCl has the smallest hydration radius, so the two composite nanofiltration membranes have the highest permeation flux and the lowest retention rate. Based on these findings, the composite nanofiltration membrane developed in this study performs well in separating divalent anions.
[0108] Effect Example 4
[0109] 1. The stability of the composite nanofiltration membrane is crucial to its practical application. Therefore, this example evaluates the permeability and selectivity of the NIP-0.5 composite nanofiltration membrane prepared by a non-traditional interfacial polymerization method under different operating times, pressures and feed solution concentrations.
[0110] In order to determine the stability of the composite nanofiltration membrane, the following three nanofiltration membrane separation stability performance tests were carried out; the specific tests are as follows:
[0111] (1) The permeability and retention rate of the composite nanofiltration membrane for 2000 ppm Na2SO4 solution were recorded during the 24 h test period to analyze the long-term stability of the composite nanofiltration membrane.
[0112] (2) 2000 ppm Na2SO4 solution was separated at different operating pressures (2, 4, 5, 6, and 8 bar), and the permeability and retention rate were recorded to evaluate the pressure resistance of the composite nanofiltration membrane.
[0113] (3) Separate Na2SO4 solutions of different concentrations (1000, 2000, 3000, 4000 ppm) and test their rejection performance. The permeability and retention rate are calculated by the above formula (3) and formula (4).
[0114] The results are as follows Figure 6 As shown in (a), after running at a pressure of 0.5 MPa for 24 h, the permeability and selectivity of the NIP-0.5 membrane remained almost unchanged, showing excellent resistance to concentration polarization. Figure 6 b shows that with the increase of pressure (2-8 bar), the permeation flux of NIP-0.5 membrane increases almost linearly, and the linear fitting determination coefficient (R 2) was 0.991, while its rejection rate remained almost unchanged. This shows that the polyamide layer of the NIP-0.5 membrane remained intact and maintained a high separation efficiency at both low and high pressures.
[0115] 2. By changing the feed solution concentration (1000, 2000, 3000, 4000ppm) to simulate different high-salinity wastewater, the NIP-0.5 membrane always showed strong rejection performance, with a retention rate of more than 99% ( Figure 6 c).
[0116] 3. The antifouling performance of the membrane directly determines its service life. In order to study the recyclability of nanofiltration membranes produced by traditional and non-traditional interfacial polymerization methods in the desalination process, IP-1 and NIP-0.5 were subjected to cyclic tests, including pure water penetration, contaminated liquid penetration and subsequent cleaning.
[0117] In this study, the antifouling performance of the composite nanofiltration membrane was evaluated by separating 1000 ppm BSA solution.
[0118] The specific steps are as follows: First, cut the composite nanofiltration membrane into a suitable size, then install it on the cross-flow device, and pre-press it at a pressure of 6 bar for a period of time, waiting for the permeability of the composite membrane to stabilize. Subsequently, adjust the pressure of the cross-flow device to 5 bar, and measure its pure water flux Jw1. Finally, replace the water solution with BSA solution for 1 hour to carry out the pollution experiment. Rinse the contaminated composite nanofiltration membrane continuously with flowing ultrapure water for a period of time until the permeability of the composite membrane stabilizes, and then test its pure water flux Jw2, that is, complete a cycle of anti-fouling performance test.
[0119] The specific calculation formula is as follows:
[0120]
[0121] Where Jw is the pure water flux of the composite nanofiltration membrane (Lm -2 -h -1 ), V is the volume of solution passing through the effective area of the composite nanofiltration membrane within a certain period of time (L), Δt (h) is the running time, and A is the effective filtration area of the composite nanofiltration membrane (the effective filtration area in this experiment is 3.4×10 -4 m 2 ). FRR is the flux recovery rate of the composite nanofiltration membrane.
[0122] The flux recovery ratio (FRR) of the membrane is Figure 6d. Compared with the IP-1 membrane, the NIP-0.5 membrane has a significantly higher flux recovery ratio in the first cycle, which is 96.2% compared to 86% for IP-1. Even after three cycles, the FRR of the NIP-0.5 membrane remains at 93.2%, while the FRR of the IP-1 membrane drops to 81.8%.
[0123] These results show that the nanofiltration membranes prepared by non-traditional interfacial polymerization have excellent antifouling properties, which is mainly attributed to the enhanced hydrophilicity and smoother surface of the NIP-0.5 membrane. The hydrophilic layer promotes water penetration and prevents pollutants from clogging the pores, while the smoother surface minimizes surface roughness (as shown in the aforementioned atomic force microscopy images), reducing the possibility of pollutant embedding. In addition, the inner cavity structure promotes the rapid transport of pollutants through the PA layer, making it less likely for pollutants to accumulate in the membrane separation layer and cause irreversible fouling.
[0124] Example 2
[0125] On the basis of Example 1, different concentrations of CaCl2 particles (5, 10 and 20 wt%) were added to the 0.5 wt% PIP aqueous solution, and the regulating effect of inorganic salt particles was utilized in the interfacial process. Following the same steps as described above, a Ca-NIP-0.5 composite nanofiltration membrane with ultrahigh permeability was successfully prepared.
[0126] Effect Example 5
[0127] Scanning electron microscopy results ( Figure 7 a) Clearly shows the membrane structure of PAN nanofibers based on Ca-NIP-0.5 membrane (CaCl2 concentration 10 wt%). At higher magnification, nodular and crater-like structures with a diameter of about 1 μm are visible on the membrane surface, which are smaller than those observed on the NIP-0.5 membrane ( Figure 7 b). In addition, compared with the membrane without CaCl2 particles, the PA separation layer of the Ca-NIP-0.5 membrane is thinner, only 61nm ( Figure 7 c).
[0128] The nanofiltration performance of the prepared Ca-NIP-0.5 composite nanofiltration membrane was then evaluated, and the results are shown in Figure 8 a and Figure 8 b. The results show that under an operating pressure of 0.5 MPa, the addition of inorganic salt CaCl2 has a significant positive effect on improving the permeability of the composite nanofiltration membrane prepared by the NIP method. When the CaCl2 concentration is 10%, the permeation flux of the Ca-NIP-0.5 membrane for 2000 ppm Na2SO4 solution reaches 33.3 LHM, which is an increase of nearly 64% compared with the NIP-0.5 membrane. This improvement can be attributed to the Ca in the inorganic salt. 2The complexation reaction between the + ions and the carbonyl groups in the TMC monomer and the selective separation layer. This reaction helps to activate the acyl chloride groups and promotes the formation of a porous selective separation layer. In addition, the activation and hydrolysis of the acyl chloride groups make the membrane surface more hydrophilic. The combination of a thinner separation layer, a larger average surface roughness, and a negatively charged membrane surface further improves the permeation flux of the Ca-NIP-0.5 membrane. This effectively alleviates the impact of the trade-off effect between permeability and selectivity, allowing the membrane to maintain good rejection performance for Na2SO4 solutions and achieve effective separation of divalent anions.
[0129] also, Figure 8 The experimental results in c show that the Ca-NIP-0.5 composite nanofiltration membrane exhibits excellent long-term stability. Figure 8 As shown in (d), the permeation flux of the composite membrane increases almost linearly with the increase of pressure. In conclusion, the non-traditional interfacial polymerization method not only shows great potential in improving the permeability of nanofiltration membranes, but also provides the opportunity to add more environmentally friendly water additives to further improve the overall performance of the membrane.
[0130] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a composite nanofiltration membrane, characterized in that: The preparation method comprises the following steps: 1) fixing the nanofiber membrane on an isolation carrier, then immersing the nanofiber membrane in an aqueous solution, and then taking out and removing excess aqueous solution on the surface of the nanofiber membrane to obtain a treated membrane A; 2) Inverting the treated membrane A and soaking it in an organic phase solution, and the aqueous phase solution soaked on the nanofiber membrane undergoes an interfacial polymerization reaction with the organic phase solution to obtain a treated membrane B; 3) heat-treating the treated membrane B to obtain a composite nanofiltration membrane.
2. The preparation method according to claim 1, characterized in that: The nanofiber membrane is at least one of polyacrylonitrile, polysulfone, and polyethersulfone nanofiber membranes.
3. The preparation method according to claim 1, characterized in that: The aqueous phase solution includes an amine compound and an acid absorbent; preferably, the amine compound is at least one of piperazine, m-phenylenediamine, polyethyleneimine, ethylenediamine, and phenylenediamine; Preferably, the acid absorbent is at least one of triethylamine, tripropylamine, N,N-diisopropylethylamine, calcium bicarbonate, and sodium hydroxide.
4. The preparation method according to claim 3, characterized in that: The mass ratio of the amine compound to the acid absorbent is 0.2 to 2:1; Preferably, the concentration of the amine compound is 0.2 to 2 wt % based on the total mass of the aqueous solution; Preferably, based on the total mass of the aqueous solution, the concentration of the acid absorbent is 0.5-1.5 wt %.
5. The preparation method according to claim 3, characterized in that: The aqueous phase solution also includes an inorganic salt; Preferably, the inorganic salt is calcium chloride; Preferably, based on the total mass of the aqueous solution, the concentration of calcium chloride is 5 to 20 wt %.
6. The preparation method according to claim 1, characterized in that: The organic solution includes an organic monomer; Preferably, the organic monomer is an acyl chloride compound; Preferably, the acyl chloride compound includes at least one of trimesoyl chloride, adipoyl chloride and isophthaloyl chloride; Preferably, the solvent of the organic solution is an organic solvent; Preferably, the organic solvent is at least one of n-hexane, cyclohexane, n-heptane, petroleum ether and dichloromethane.
7. The preparation method according to claim 6, characterized in that: Based on the total weight of the organic solution, the organic solution contains 0.1-0.5 wt% of organic monomer, and the remainder is organic solvent.
8. The preparation method according to claim 1, characterized in that: The infiltration time in step 1) is 40 to 80 seconds; Preferably, the infiltration time in step 2) is 20 to 40 seconds; Preferably, the temperature of the heat treatment is 50-70° C.; and / or the time of the heat treatment is 10-20 min.
9. A composite nanofiltration membrane, characterized in that: The composite nanofiltration membrane is prepared by the method according to any one of claims 1 to 8.
10. Use of the composite nanofiltration membrane prepared by the method described in any one of claims 1 to 8 or the composite nanofiltration membrane described in claim 9 in the field of water treatment; preferably used in seawater desalination pretreatment, drinking water purification, industrial and / or domestic wastewater treatment, food industry and / or medicine.
Citation Information
Cited By
Aromatic polyamine nanofiltration membrane, preparation method thereof and application of aromatic polyamine nanofiltration membrane in separation of antibiotics and inorganic salts
CN121513670A